DAMPAK KEHADIRAN PT. SORIK MARAPI GEOTHERMAL POWER (SMGP) DI KECAMATAN PUNCAK SORIK MARAPI - Rizky Harianti; Halimatussakdiah Halimatussakdiah; Lia Wardani; Siti Khodijah Nasution (LPPM UIKA Bogor, 2021)
ABSTRACT This study aims to determine the opinion and also the response of the community about the construction of the Sorik Marapi Geothermal Power Company (SMGP) in Puncak Sorik Marapi District, Mandailing Natal Regency. In addition, to find out how the SMGP Company's impact the welfare of the surrounding community. The research method used includes the qualitative description method to assess the positive and negative impacts of the company. Data collection was obtained through the distribution of questionnaires containing questionnaires, interviews, and observations. The results of the study stated that most of the people did not agree with the existence of this SMGP company so that there were many polemics between the community and the company. The polemics that occurred included polemics in the fields of economy, health, education, and politics, and it also did not rule out other fields such as social, culture and tradition. The lack of socialization from the company to the public creates misunderstandings so that various polemics arise in the community, especially for people who do not work at the company. And various politics occur in society, one of which is concerned with personal and group interests, and some groups take advantage of such situations. Key Word: Impact, Presence, Polemic